Insights into dye design for efficient p-type photoelectrodes: effect of oligothiophene length between the donor and the NiO surface. Issue 113 (2nd November 2015) - Wu, Fei; Zhao, Shangbi; Zhong, Cheng; Song, Qunliang; Zhu, Linna
Abstract : T4 with tetra-thiophene as a spacer show the highest performance, while further increased oligothiophene length result in decreased efficiency. Abstract : We report experimental studies of "push–pull" organic dyes with three to six thiophene units as π-spacers, and their application as p-type sensitizers for dye-sensitized solar cells. Different from the widely explored model of increasing spacer length between donor and acceptor, in this paper, the distance between the donor and the semiconductor surface is elongated by inserting thiophene units. The effect of the increased π-spacer is systematically discussed. It turned out that four thiophene units could offerT4 with the highest performance. Further increased length instead, results in decreased J sc values and finally decreased efficiencies. We estimate that the longer spacer could effectively prevent charge recombination on the NiO-dye surface, however, the increased thiophene units also decrease the conductance of the oligothiophene spacer, which is unfavorable for hole injection from dye molecule to the valence band of NiO. The results demonstrate that the distance between donor and the semiconductor should be optimized. The appropriate length is required to balance charge recombination and charge transporting efficiency.